Perbedaan Prestasi Belajar Matematika Ditinjau dari Tipe Kepribadian Siswa dalam Pembelajaran Matematika - Dwi Oktaviana; Utin Desy Susiaty (SAP (Susunan Artikel Pendidikan), 2017)
This study aims to find significant differences in mathematics learning achievement of students with personality types (Sanguine, Melancholic, Choleric, Phlegmatic). It is a quasi-experimental study using Factorial Design as its research design. The population of this study is all students from class X MIA SMA Negeri 3 Pontianak. Samples are taken applying a purposive sampling technique. The collected data are in the form of mathematics learning achievement and questionnaire. The scores oflearning achievement are obtained from multiple-choice tests. The questionnaire distributed is a test of personality types (Sanguine, Melancholic, Choleric, Phlegmatic). Data are analyzed using One Way Analysis of Variance (Anova). The results show there are significant differences in mathematics learning achievement of students with personality types (Sanguine, Melancholic, Choleric, Phlegmatic), as proved in the results of the analysis fh = 0,139 < ft = 2,92.